Analisis Kandungan Vitamin C Buah Naga Merah (Hylocereus polyrhizuz) dan Buah Naga Putih (Hylocereus undatus) pada Penyimpanan dengan Suhu dan Waktu yang Berbeda - Sumaryani, N. Putri; Dharmadewi, Anak Agung Istri Mirah (Metamorfosa: Journal of Biological Sciences; Vol 5 No 2 (2018)DO - 10.24843/metamorfosa.2018.v05.i02.p18, 2018)
This study was conducted to determine the temperature and storage time of the exact vitamin C content of red and white dragon fruit and the difference of vitamin C. The samples were taken from the plantation land in Ubud Andong Highway, Petulu, Gianyar Regency. Treated for 10 and 30 days with 2, 10, 20 and 30 0 C temperature treatment with five repetitions using Completely Randomized Design Factorial pattern. Data obtained statistically using ANOVA (Analysis of Variance). The highest vitamin C content in red dragon fruit is 29.61 mg/ 100g temperature 10 0 C for 10 days and the lowest is in 30 days storage with temperature 30 0 C that is equal to 22,09 mg/ 100g. While the white dragon fruit content of vitamin C highest contained in storage with a temperature of 2 0 C is 22.69 mg/ 100g with maximum storage of 10 days and the lowest at a temperature of 30 0 C is 17.37 mg/ 100g.